Stability and bifurcations in Kerr-lens mode-locked Ti:sapphire lasers - Kovalsky, Marcelo Gregorio (2000)
Kerr-lens or self-mode-locked Ti:sapphire lasers are known to display several modes of operation, depending on the values taken by the system's parameters. The basic observed modes of operation are: continuous wave, mode locking with transform limited pulses, and mode locking with chirped pulses. These modes are naturally obtained from a description based on an iterative or Poincare map of five pulse variables (beam size curvature, pulse duration, chirp and energy). The stability of these modes is obtained for an experimentally accessible range of the parameters. The theoretical predictions agree qualitatively with the experimental observations. For a particular bifurcation, we study the feasibility of an approximate description of the (five variables) dynamics with a one-variable map, which results in the logistic map.